Hubungan Mindful Eating dan Tingkat Stres dengan Status Gizi pada Siswa SMA Global Persada Mandiri School: Correlation between Mindful Eating and Stress Level with Nutritional Status in Global Persada Mandiri High School Students - Maharani, Triayu; Khomsan, Ali (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2024)
Emotional eating is a coping strategy for stress management that can lead to excessive food intake, while mindful eating is a preventive measure. This study aims to analyze the correlation between mindful eating and stress levels with the nutritional status of Global Persada Mandiri (GPM) High School students. This research design used a cross-sectional design involving 113 GPM high school students. Subject characteristics, mindful eating, and stress levels were obtained through questionnaires and interviews. Anthropometry data were obtained by direct measurement. Most of the research subjects had low mindful eating practices (90.27%) and moderate stress level (83.19%). The nutritional status of research subjects was dominated by good nutrition (61.06%). The results of the Spearman Rank correlation test showed no significant correlation between the MEQ total score and MEQ domains, awareness, distraction, disinhibition, and external cues with nutritional status (p>0.05). There is a significant negative correlation between the MEQ domain, emotional response, and nutritional status (p<0.05). No significant correlation was found between stress levels and nutritional status (p>0.05). However, the correlation test results for energy intake and nutritional status showed a significant positive correlation (p<0.05).